THE IMPORTANCE OF THE SOCIAL WORKER FOR PUBLIC HEALTH FACING THE CHALLENGES FOUND IN SUS - da Silva Claro, Luciana (Revista Gênero e Interdisciplinaridade, 2021)
The importance of the social worker inserted in public health, especially in face of the current confrontations of SUS (Unified Health System), aims to report within the context, crucial points that social service professionals experience in the practice of this area and their strategies to excel Of the various problems that surround them in this action. Therefore, it is essential to address the totality of actions that are developed by social workers in health, considering the particularity of the actions performed in the health programs as well as in basic care, in the medium and high complexity in health. On the other hand, the option not to structure it in front of these work fronts that seek to surpass the register of actions that are common within these, and tend to be repeated when the perspective is to indicate the attributions of professionals in health. Based on the code of ethics of the profession of 1993, the attributions and competences of the social worker are fundamental, either in health or in the most diverse public policies of action, emphasizing theoretical and practical achievements, addressing a more critical, participatory, dialectical and reflexive professional universe . Within the theoretical basis were addressed the following points: as Unified Health System and the impositions for social workers; SUS and professional ethics; The professional work of the social worker and the expanded conception of health; SUS the current trajectory and challenges, in order to establish information and promote strategies to be implemented in the field of basic public health care.Keywords: Importance, Social Worker, Public Health, Challenges, SUS.